Intercultural screen adaptation : British and global case studies - Stewart, Michael Patrick James; Munro, Robert (Film scholar) (Edinburgh University Press, 2020)
Intercultural Screen Adaptation offers a wide-ranging examination of how film and television adaptations (and non-adaptations) interact with the cultural, social and political environments of their national, transnational and post-national contexts. With screen adaptations examined from across Britain, Europe, South America and Asia, this book tests how examining the processes of adaptation across and within national frameworks challenges traditional debates around the concept of nation in film, media and cultural studies. With case studies of films such as Under the Skin (2013) and T2: Trainspotting (2017), as well as TV adaptations like War and Peace (2016) and Narcos (2015 - 2017), Intercultural Screen Adaptation offers readers an invigorating look at adaptations from a variety of critical perspectives, incorporating the uses of landscape, nostalgia and translation.